Implementasi Pendidikan Agama Islam Bagi Siswa Tunanetra - Sari, Lailli Irna; Wibawa, Zakki Teguh; Jaistyurohman, Robbit Azam; Alamsyah, Dani (Lembaga Yasin AlSys, 2021)
Education is an aspect that must be accepted by children so that later they are not wrong in taking steps to take the next life. Islamic religious education itself is an education that must be known by every child so that it becomes a guide for the life to come. This journal will discuss the material